Distinct evolution of TLR-mediated dendritic cell cytokine secretion in patients with limited and diffuse cutaneous systemic sclerosis. Issue 8 (24th May 2010) - van Bon, L; Popa, C; Huijbens, R; Vonk, M; York, M; Simms, R; Hesselstrand, R; Wuttge, D M; Lafyatis, R; Radstake, T R D J
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease and accumulating evidence suggests a role for Toll-like receptor (TLR)-mediated activation of dendritic cells (DCs). Objective: To map TLR-mediated cytokine responses of DCs from patients with SSc. Methods: 45 patients with SSc were included. Patients were stratified as having diffuse cutaneous SSc (dSSc) or limited cutaneous SSc (lSSc) according to the extent of skin involvement, and further divided into those with late (>3 years) or early disease (<2 years). DCs were stimulated with ligands for TLR2, TLR3, TLR4, TLR7/8 or combinations. Plasma samples were collected from patients with SSc (n=167) and measured for interleukin 6 (IL-6), tumour necrosis factor α (TNFα), IL-12, IL-10 and interferon γ. Results: Stimulation of DC subsets from patients with early lSSc and dSSc with ligands for TLR2, TLR3 or TLR4 resulted in higher secretion of IL-6 and TNFα compared with those having late disease or healthy controls. Remarkably, the production of IL-12 was lower upon stimulation with TLR ligands in most patients with SSc, whereas the secretion of IL-10 was very high in patients with the dSSc phenotype, particularly in those having early dSSc. The combination of various TLR ligands led to reduced cytokine secretion in all patients with SSc. Circulating levels of these cytokines further underscored the presence of differences between various SSc phenotypes. Discussion: The altered TLR-mediated activation of DCs may be responsible for Th2 skewed T-cell activation in SSc that may be orchestrated by fibrogenic T-cell cytokines, such as IL-4 and IL-13. DC targeting could thus offer new avenues for therapeutic intervention.